2020
DOI: 10.3390/ma13173749
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies, Young’s Modulus and Resistivity of High Aspect Ratio Tungsten Nanowires

Abstract: High aspect ratio tungsten nanowires have been prepared by selective dissolution of Nickel-aluminum-tungsten (NiAl−W) alloys which were directionally solidified at growth rates varying from 2 to 25 μm/s with a temperature gradient of 300 K·cm−1. Young’s modulus and electrical resistivity of tungsten nanowires were measured by metallic mask template method. The results show that the tungsten nanowires with uniform diameter and high aspect ratio are well aligned. The length of tungsten nanowires increases with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Tungsten nanowires are another type of morphology. They are produced by a range of methods, including the hard templating by mesoporous silica SBA-15 [36] or mesoporous carbon [37], the chemical vapor transport process from W filament [38], Ni-catalyzed vapor-phase decomposition of WO 2 (OH) 2 [39,40], decomposition of W(CO) 6 or WF 6 by a focused ion beam [41,42], electric field [43,44], and an electron beam [45][46][47], carbothermal reduction of WO 3 /CTAB lamellar composites [48], and especially by directional solidification and selective electrochemical dissolution of NiAl-W eutectic alloys [49,50] resulting in single-crystalline nanowires with extraordinary lengths and diameters around 200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten nanowires are another type of morphology. They are produced by a range of methods, including the hard templating by mesoporous silica SBA-15 [36] or mesoporous carbon [37], the chemical vapor transport process from W filament [38], Ni-catalyzed vapor-phase decomposition of WO 2 (OH) 2 [39,40], decomposition of W(CO) 6 or WF 6 by a focused ion beam [41,42], electric field [43,44], and an electron beam [45][46][47], carbothermal reduction of WO 3 /CTAB lamellar composites [48], and especially by directional solidification and selective electrochemical dissolution of NiAl-W eutectic alloys [49,50] resulting in single-crystalline nanowires with extraordinary lengths and diameters around 200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[87,88] Compared to the conventional rigid electrodes, the elastic modulus of Ga-based LM electrodes is relatively close to the soft neural tissue. [89] Guo et al developed an implantable neural microelectrode array, comprising In-Ga alloy electrodes and 500 μm polydimethylsiloxane (PDMS) encapsulation. [90] The authors demonstrated that the LM electrodes with PDMS exhibit elastic modulus similar to that of the dura mater and skin by analyzing the stress-strain curve.…”
Section: Viscoelasticitymentioning
confidence: 99%
“…[ 87,88 ] Compared to the conventional rigid electrodes, the elastic modulus of Ga‐based LM electrodes is relatively close to the soft neural tissue. [ 89 ] Guo et al. developed an implantable neural microelectrode array, comprising In‐Ga alloy electrodes and 500 µm polydimethylsiloxane (PDMS) encapsulation.…”
Section: Properties Of Ga‐based Lms For Bioelectronicsmentioning
confidence: 99%